The efficacy and molecular mechanism of the effect of schisandrin b on the treatment of erectile dysfunction - WEI LIU; CHEN ZHAO; Yanping Huang; Yidong Liu; Mujun Lu (Iranian Journal of Basic Medical Sciences, 2019)
Objective(s): The purpose of this study is to determine the efficacy and molecular mechanism of the effect of schisandrin b (SCHB) on treating erectile dysfunction (ED) in a rat model with bilateral cavernous crushing nerve injury. Materials and Methods: The ED rat model was established with bilateral cavernous nerve crushing, and then confirmed by apomorphine. Fifty healthy eight-week-old ED rats were randomly assigned into five group, including control group (sham surgery), bilateral cavernous nerve crushing injury group (BCNC), BCNC with low SCHB (100 mg/d), BCNC with medium SCHB (200 mg/d) and BCNC with high SCHB (400 mg/d). For the last three groups, SCHB was given for 2 months. Then, we examined intracavernosal pressure (ICP), cyclic nucleotides (cAMP, cGMP), endothelial nitric oxide synthase (eNOS) and neuronal NOS (nNOS) in all groups. Results: In the study of ICP, SCHB was able to improve ED in a dose-dependent manner. In addition, as compared to the BCNC group, the relative expression of eNOS and nNOS in medium and high concentration of SCHB-treated groups are higher than BCNC group. Moreover, all groups treated with SCHB showed a significant higher expression level of cAMP and cGMP.Conclusion: These results suggested that SCHB were able to significantly improve the ED on rat model through the NO-cGMP and cAMP- protein kinase A (PKA) pathway.